Gumpang Temple as a source of ethnomathematics learning - Sutrimo, Sutrimo; Kamid, Kamid; Asrial, Asrial; Hariyadi, Bambang (International Journal of Trends in Mathematics Education Research, 2023)
This study aims to explore the Gumpang Temple as a source of learning mathematics for geometry in junior high school. The form of learning that comes from nature is ethnomathematics. The researcher describes how the Gumpang Temple will be a fun and exciting source of learning. This study uses a qualitative approach. Data collection was obtained by observation and literature sources. The data findings were analyzed using qualitative data analysis with descriptive methods. The results of this study indicate that the wealth of ethnomatematic literature using Gumpang Temple is quite a lot. Various approaches and formulas can be applied to the teaching of geometry. These findings lead researchers to conduct further research to explore the manufacture of teaching materials using different research approaches.